Psychosocial Health Levels and Substance Use Frequency of Intern Students Studying Health Sciences in Turkey - Demirel, Gülbahtiyar; Taşkın Yılmaz, Feride; Şimşek, Gamze Nur (Addicta: The Turkish Journal on Addictions, 2020)
This study was conducted to determine the psychosocial health levels, substance use frequency, and factors affecting the students in the faculty of health sciences. A total of 681 senior year students studying in the faculty of health sciences in Sivas Cumhuriyet University between March 20 and April 15, 2018 were included in this descriptive and cross-sectional study, which constituted 86.4% of the students at the university. Data were collected using student identification form, depression anxiety stress scale, and substance use information form. Student t, Mann-Whitney U, Chi-squared, and Kruskal-Wallis tests, ANOVA, and Pearson correlation analysis were used for statistical evaluation. It was determined that 16.9% of the students used substances such as cigarettes, alcohol, narcotic drugs, and heroin/hashish during internship. The depression and stress levels were found to be normal, and the anxiety levels were mild according to the students' depression, anxiety and stress scale mean scores; 14.2% of the students had severe depression, 20.9% had severe anxiety, and 9.4% had severe stress. Depression, anxiety, and stress levels of students who used substances were found to be higher. The students preferred smoking, alcohol, and substance use as a coping method due to the psychosocial problems.
Keywords: Anxiety; depression; health sciences; student; substance